Scale up the biopolymer (PHB) fermentation from shake flasks to 10l stirred tank fermenter - Goh, Mei Fong (2008)
Plastics have been an integral part of our life. However, disposal of these non-biodegradable (petrochemical derived) plastics poses a threat to our environment. In an effort to overcome these shortcomings, biochemical researchers and engineers have long been seeking to develop biodegradable plastics that are made from renewable resources. Polyhydroxybutyrates (PHB) are polymers that accumulate as carbon and energy in Cupriavidus necator and provide an alternative to petrochemical plastic because of their biodegradability properties. However, major problems in commercializing PHB is the high production cost due to expensive carbon substrates and tedious production procedures using pure cultures. Therefore, the applications of mixed cultures and cheap carbon sources have been explored. In this study, the biopolymer fermentor has to scale up from shake flask to 10L of stirred tank fermentor. This is to increase the mass production of PHB that produced by Cupriavidus necator. The biopolymer fermentor is scaled up is by fixing the “kLa”. kLa value were derived by fitting the mass transfer equation to the data of dissolved oxygen tension (DOT) versus time on computer using Matlab method with two unknowns, namely kLa and the electrode mass transfer coefficient (kLa) of oxygen. The stirred speed (rpm) and the air flow rate (A) in the 10L fermentor that produced the value of kLa found in the optimized conditions in shake flask was approximated by trail an error. Overall, scale up by using the method of constant volumetric oxygen transfer coefficient (kLa) in the 10L stirred tank fermentor will produce the same PHB production as in the shake flask.